Reconstructing the Purpose of Sentencing: Rethinking the Effectiveness of Imprisonment in the Contemporary Legal System (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: Indonesia's criminal justice system still places imprisonment as the primary sanction, although its effectiveness is increasingly questioned. The high occupancy rates in correctional facilities, the burden on the state budget, and weak social reintegration indicate a mismatch between the idealized goals of criminal punishment and the reality of practice. This situation calls for a reevaluation of the relevance of prison sentences within the framework of contemporary criminal law.Purposes of the Research: This study aims to re-examine the effectiveness of prison sentences within the framework of Indonesian criminal law following the latest codification, by considering their suitability in relation to the objectives of modern sentencing. The focus is on formulating a prison sentence concept that is proportional, measurable, and oriented towards rehabilitation and social reintegration, making it relevant for the development of criminal law theory and national policy.Methods of the Research: This research uses a normative legal method, focusing on a doctrinal study of statutory regulations, doctrines, and criminal law literature. The approaches used include legislative, conceptual, and comparative approaches to examine the effectiveness of imprisonment and its relevance within the framework of the 2023 Criminal Code, resulting in a systematic, measurable, and academic analysis.Findings of the Research: This study highlights the opportunity to reorganize the orientation of criminal sanctions through the latest codification of criminal law. Imprisonment, no longer dominant, becomes a last resort for minor offenses. Normative analysis reveals the weaknesses of prison, encouraging alternative penalties. This study reconstructs the objectives of criminal sanctions, offering a concept that is more proportional, rehabilitative, and relevant to the needs of national law and policy.